PRINSIP-PRINSIP SOPAN SANTUN DALAM BAHASA INGGRIS DAN BAHASA BAJO (ANALISIS KONTRASTIF) - S. Maja, DELTA; KODONG, FENTJE; LASUT, THERESIA M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œPoliteness Principles in English and Bajo language: A Contrastive Analysis.â€ This study is an attempt to identify, classify, analyze and contrast polite utterances in English and Bajo language according to politeness principles. In this research, the writer uses descriptive method. The English data were collected from pragmatic books, website and some skripsis, and Bajo language data have been collected by interviewing the native speakers of Bajo language who live in Kalupapi Village, from some books and website. In this research the write uses Leechâ€™s theory in analyzing data and Ladoâ€™s theory in contrasting both languages to find out the differences and similarities in both languages. The polite principles in both languages that can be seen are requesting, commanding and ordering, and it is also shown by the acting of convincing what the speaker says. It is expected that this study can help the students and readers in learning politeness principles in using language in daily life.Â Â Keywords: Politeness Principle, Pragmatics, Contrastive Analysis, Bajo Language.